2010
DOI: 10.1149/1.3261855
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Catalyst Supports Deposited on Nanostructured Thin Films for Proton Exchange Membrane Fuel Cells

Abstract: A series of platinum-coated underlayer materials, alumina, gold, titanium carbide, and titanium disilicide, deposited by a high throughput magnetron sputtering method have been investigated as cathode catalyst supports in fuel cells. Orthogonal thickness gradients of the underlayer materials ͑0-100 nm planar equivalent͒ and the platinum top layer ͑0-75 nm planar equivalent͒ made up the 76 ϫ 76 mm libraries. The resulting catalyst films were characterized by surface profilometry, X-ray diffraction, scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It has been reported that Pt monolayer catalysts, such as Pt ML /Pd/NiW/GDL and Pt ML /Pd/C, showed excellent durability in PEMFC tests [64], but their H 2 /Air performance needs further improvement by optimizing the ionomer distribution in the catalyst layer. The 3M nanostructured thin film (NSTF) catalyst is currently the sole practical example of an extended surface area catalyst shown to effectively address several critical issues facing cathode and anode catalysts for fuel cell vehicles, including the performance, cost, and durability [67]. The NSTF Pt68Co29Mn3 catalyst has been the workhorse cathode and anode of choice for a number of years and its CCM [68,69] generated a specific activity of 2.93 mA/cm 2 Pt and a mass activity of 0.18 A/mgPt at 0.9 V vs. RHE.…”
Section: Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that Pt monolayer catalysts, such as Pt ML /Pd/NiW/GDL and Pt ML /Pd/C, showed excellent durability in PEMFC tests [64], but their H 2 /Air performance needs further improvement by optimizing the ionomer distribution in the catalyst layer. The 3M nanostructured thin film (NSTF) catalyst is currently the sole practical example of an extended surface area catalyst shown to effectively address several critical issues facing cathode and anode catalysts for fuel cell vehicles, including the performance, cost, and durability [67]. The NSTF Pt68Co29Mn3 catalyst has been the workhorse cathode and anode of choice for a number of years and its CCM [68,69] generated a specific activity of 2.93 mA/cm 2 Pt and a mass activity of 0.18 A/mgPt at 0.9 V vs. RHE.…”
Section: Catalystsmentioning
confidence: 99%
“…The mass activities of the NSTF Pt3Ni7 for ORR with standard treatment cover the range of 0.35 to 0.59 A/mg [70]. A proprietary GM additional pretreatment process can further substantially increase the mass activities over the standard treatment; 0.47 to 0.58 A/mg using the GM ORR protocol and 0.62 to 0.67 A/mg using the 3M protocol [67]. However, even though reasonable current densities are being realized at 650 mV in PEMFCs, the limiting current densities are still not optimally high.…”
Section: Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are composed of arrays of small (less than 1 µm length) organic whiskers, fully covered by a thin Pt or Pt‐based alloy catalyst layer (see Figure (b) and next section). 3M layers exhibit very promising performance in PEMFCs and have been subject of numerous original and review papers . Inspired by the success of the NSTFs, several groups came up with alternative structures.…”
Section: Introductionmentioning
confidence: 99%
“…3M layers exhibit very promising performance in PEMFCs and have been subject of numerous original and review papers. [37][38][39] Inspired by the success of the NSTFs, several groups came up with alternative structures. For example, in order to further decrease the amount of PGMs, it was proposed to co-sputter Pt with carbon 40 (Figure 1(c)), or to deposit it on spatially ordered carbon nanostructures, such as vertically aligned carbon nanotubes or nanofibers 32 (Figure 1 (d) and (e)).…”
Section: Introductionmentioning
confidence: 99%